A Comparison of the Performance and Status of the Manufacturing Managed by Cooperatives Using Good Manufacturing Practices for Ribbed Smoked Sheets and Cooperatives Not Using Good Manufacturing Practices for Ribbed Smoked Sheets: ผลการดำเนินงานและสถานภาพการผลิตยางแผ่นรมควันของสหกรณ์กองทุนสวนยาง ที่ได้รับและไม่ได้รับมาตรฐานการปฏิบัติที่ดีสำหรับการผลิตยางแผ่นรมควัน: กรณีศึกษาจังหวัดตรังและสงขลา - Satsue, Palakorn; Phitthayaphinant, Purawich (Journal of Applied Economics and Management Strategy, 2019)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อวิเคราะห์ผลการดำเนินงาน รวมทั้งประเมินการปฏิบัติตามการปฏิบัติที่ดีสำหรับการผลิตยางแผ่นรมควัน ตลอดจนวิเคราะห์ปัจจัยภายในและภายนอกที่มีผลต่อการผลิตยางแผ่นรมควันของสหกรณ์กองทุนสวนยางที่ได้รับและไม่ได้รับมาตรฐานการปฏิบัติที่ดีสำหรับการผลิตยางแผ่นรมควัน โดยใช้สหกรณ์กองทุนสวนยางวังคีรี จำกัด จังหวัดตรัง และสหกรณ์กองทุนสวนยางท่าข้ามพัฒนายาง จำกัด จังหวัดสงขลาเป็นกรณีศึกษา ข้อมูลทุติยภูมิที่ใช้เป็นข้อมูลทางการเงินประจำปีบัญชี 2558 ส่วนการรวบรวมข้อมูล ปฐมภูมิใช้แบบสัมภาษณ์เชิงโครงสร้าง การสนทนาตามธรรมชาติ การสนทนากลุ่ม และการสังเกตแบบไม่มีส่วนร่วม ผู้ให้ข้อมูลหลัก คือ ประธานกรรมการสหกรณ์ คณะกรรมการสหกรณ์ เจ้าหน้าที่สหกรณ์ และสมาชิกสหกรณ์จำนวน 30 คน ซึ่งใช้การเลือกแบบเจาะจง การวิเคราะห์ข้อมูลใช้อัตราส่วนทางการเงิน ค่าเฉลี่ย และการวิเคราะห์สวอท ผลการวิจัยพบว่า สหกรณ์กองทุนสวนยางวังคีรี จำกัดมีความสามารถในการทำกำไรสูงกว่าสหกรณ์กองทุนสวนยางท่าข้ามพัฒนายาง จำกัด สหกรณ์กองทุนสวนยางวังคีรี จำกัดมีการปฏิบัติตามการปฏิบัติที่ดีสำหรับการผลิตยางแผ่นรมควันในระดับมากที่สุด ส่วนสหกรณ์กองทุนสวนยางท่าข้ามพัฒนายาง จำกัดอยู่ในระดับปานกลาง ปัจจัยที่เป็นจุดแข็ง คือ ความเพียงพอของน้ำยางสด ปัจจัยที่เป็นจุดอ่อน คือ ความไม่หลากหลายของช่องทางการจัดจำหน่าย ปัจจัยที่เป็นโอกาส คือ ความเชื่อมั่นของลูกค้าในคุณภาพยางแผ่นรมควัน และปัจจัยที่เป็นอุปสรรค คือ ความผันผวนของราคาน้ำยางสด ผลการวิจัยที่ได้สามารถนำไปใช้เป็นแนวทางในการพัฒนาการผลิตยางแผ่นรมควันของสหกรณ์กองทุนสวนยางต่อไป คำสำคัญ: เกษตรกรชาวสวนยาง การปฏิบัติที่ดีสำหรับการผลิต ยางแผ่นรมควัน สหกรณ์กองทุนสวนยาง ABSTRACT The objectives of this research were to study the performance and to investigate the implementation of good manufacturing practices (GMP) for the production of ribbed smoked sheets (RSSs). In addition, the study aimed to analyze the internal and external factors affecting ribbed smoked sheet manufactures comparing certified and uncertified Rubber Fund Cooperatives using GMP for RSSs using case studies of the Wang Khiri Rubber Fund Cooperative Ltd. in Trang province, and the Thakham Pattanayang Rubber Fund Cooperative Ltd. in Songkhla province, both in Thailand. Secondary data were financial data for fiscal year 2015. Primary data were collected using structured interviews, natural conservations, group discussions, and non-participant observations. Thirty key informants, which consisted of the chairmen of the cooperatives, members of cooperative committees, cooperative officials, and cooperative members, were collected using purposive selection. Financial ratios, average, and SWOT analysis were used for the data analysis. The results revealed that the profitability of the Wang Khiri Rubber Fund Cooperative Ltd. was higher than that of the Thakham Pattanayang Rubber Fund Cooperative Ltd.. The Wang Khiri Rubber Fund Cooperative Ltd. applied the highest level of GMP for RSSs. In addition, the Thakham Pattanayang Rubber Fund Cooperative Ltd. applied a moderate level of GMP for RSSs. The dominant strength was the adequacy of rubber latex. The dominant weakness was the limitation of distribution channels. The dominant opportunity was customers’ trust in the quality of the RSSs, and the dominant threat was fluctuation in the price of rubber latex. The results are useful for rubber fund cooperatives to develop ribbed smoked sheets. Keywords: Rubber Farmer, Good Manufacturing Practices, Ribbed Smoked Sheet, Rubber Fund Cooperative